Temporal genetic dynamics of reintroduced and translocated populations of the endangered golden lion tamarin (Leontopithecus rosalia) - Moraes, Andreia Magro (2017)
Reintroductions—captive-born animals introduced into the species’ original distribution area—and translocations—free-living animals transferred to another location within the historical distribution area—are important conservation strategies for endangered species. Genetic analyses of 239 individuals from unmanaged, translocated and reintroduced populations of Leontopithecus rosalia were performed using 14 microsatellites. These samples were collected during two periods: (a) 1996–1997 (historic), when individuals were translocated and reintroduced into forest fragments in the lowland Atlantic Forest, and (b) 2007–09 (recent). We hypothesized that effective population size and genetic diversity would increase over time and that these management strategies would affect the resulting population genetic structure. We found trends indicating that the effective population size at the translocation site increased while that at the reintroduction sites diminished over time. The inbreeding coefficient of the translocated population diminished over time (from 0.38 to 0.03) and was much lower than that of the native (0.29) and reintroduced (0.13) recent populations. We observed a greater genetic admixture among the reintroduced sites on the historic sampling, as well as a strong genetic structure at the translocation site. In the recent sampling, the population structuring became more site-related suggesting low or inconsistent gene flow between sampling sites. This research highlights how conservation management decisions have an important influence on the genetic outcome of translocations and reintroductions. Future conservation planning should consider population genetic monitoring before and after management measures and maintain population connectivity thereafter to avoid the negative effects of a population size reduction.